Impaired functional differentiation for categories of objects in the ventral visual stream: A case of developmental visual impairment. (October 2015) - Martinaud, Olivier; Pouliquen, Dorothée; Parain, Dominique; Goldenberg, Alice; Gérardin, Emmanuel; Hannequin, Didier; Altarelli, Irène; Ramus, Franck; Hertz-Pannier, Lucie; Dehaene-Lambertz, Ghislaine; Cohen, Laurent
Abstract: We report the case of a 14-year-old girl suffering from severe developmental visual impairment along with delayed language and cognitive development, and featuring a clear-cut dissociation between spared dorsal and impaired ventral visual pathways. Visual recognition of objects, including faces and printed words, was affected. In contrast, movement perception and visually guided motor control were preserved. Structural MRI was normal on inspection, but Voxel Based Morphometry (VBM) revealed reduced grey matter density in the mesial occipital and ventral occipito-temporal cortex. Functional MRI during the perception of line drawings uncovered impaired differentiation which is normally observed at even younger ages: no local category preferences could be identified within the occipito-temporal cortex for faces, houses, words or tools. In contrast, movement-related activations appeared to be normal. Finally, those abnormalities evolved on the background of chronic bilateral occipital epileptic activity, including continuous spike-wave discharges during sleep, which may be considered as the primary cause of non-specific intellectual disability and visual impairment. Highlights: We report a case of severe developmental visual impairment. Movement perception and visuo-motor control were spared. VBM revealed reduced grey matter density in the occipito-temporal cortex. fMRI showed a lack of category selectivity for faces, houses, words and tools. The deficit is related to chronic epileptic activity in occipitotemporal regions.